Genome‐wide meta‐analysis identifies susceptibility loci for autoimmune hepatitis type 1. Issue 3 (3rd June 2022) - Li, You; Sun, Ying; Liu, Yanmin; Wang, Bangmao; Li, Jia; Wang, Hanxiao; Zhang, Haiping; Wang, Xiaoyi; Han, Xu; Lin, Qiuxiang; Zhou, Yang; Hu, Lilin; et al.
Abstract: Background and Aims: Autoimmune hepatitis (AIH) is a rare and chronic autoimmune liver disease. While genetic factors are believed to play a crucial role in the etiopathogenesis of AIH, our understanding of these genetic risk factors is still limited. In this study, we aimed to identify susceptibility loci to further understand the pathogenesis of this disease. Approach and Results: We conducted a case–control association study of 1, 622 Chinese patients with AIH type 1 and 10, 466 population controls from two independent cohorts. A meta‐analysis was performed to ascertain variants associated with AIH type 1. A single‐nucleotide polymorphism within the human leukocyte antigen ( HLA ) region showed the strongest association with AIH (rs6932730: OR = 2.32; p = 9.21 × 10 −73 ). The meta‐analysis also identified two non‐HLA loci significantly associated with AIH: CD28 / CTLA4 / ICOS on 2q33.3 (rs72929257: OR = 1.31; p = 2.92 × 10 −9 ) and SYNPR on 3p14.2 (rs6809477: OR = 1.25; p = 5.48 × 10 −9 ). In silico annotation, reporter gene assays, and CRISPR activation experiments identified a distal enhancer at 2q33.3 that regulated expression of CTLA4 . In addition, variants near STAT1 / STAT4 (rs11889341: OR = 1.24; p = 1.34 × 10 −7 ), LINC00392 (rs9564997: OR = 0.81; p = 2.53 × 10 −7 ), IRF8 (rs11117432: OR = 0.72; p = 6.10 × 10 −6 ), and LILRA4 / LILRA5 (rs11084330: OR = 0.65; p = 5.19 × 10 −6 ) had suggestive association signals with AIH. Conclusions: Our study identifies two novel loci ( CD28 / CTLA4 / ICOS and SYNPR ) exceeding genome‐wide significance and suggests four loci as potential risk factors. These findings highlight the importance of costimulatory signaling and neuro‐immune interaction in the pathogenesis of AIH. Abstract :